FAKTOR YANG MEMPENGARUHI KINERJA APARATUR PEMERINTAH DESA DALAM AKUNTABILITAS DANA DESA - pratiwi, umi; Ulfah, Permata (Jurnal Riset Akuntansi dan Keuangan, 2018)
This study aims to determine whether the factors understanding the Government Regulation on Village Fund Management, Implementation of good governance government, the quality of human resources affect the performance of village government officials in the accountability of village funds. The study was carried out in villages in 3 Sub-districts in Banyumas District namely Sumbang, Patikraja and Rawalo. Data were collected through questionnaires sent to respondents who served as village heads / village secretaries / treasurers. Respondents numbered 38 people representing 38 villages in 3 Subdistricts of Banyumas Regency.Research results indicate that the factor of understanding of the Government Regulation on Village Fund Management does not affect the performance of the village government apparatus in the accountability of village funds. Variables in the application of good governance government principles and the quality of human resources influence the performance of village government officials in village fund accountabilityÂ